Design and operation of farm irrigation systems - Hoffman, Glenn J.; Evans, Robert G.; Jensen, Marvin Eli; Jensen, Derrel L. x; Elliott, Ronald L. (American Society of Agricultural and Biological Engineers, 2007)
"This edition provides the latest technology in the design of surface, sprinkler, and microirrigation systems along with basic information about soils and current information on estimating crop water requirements. New chapters have been added on planning systems, environmental issues, efficiency and uniformity, chemigation, and use of wastewater for irrigation." -- Preface.